1995
DOI: 10.1104/pp.109.3.1017
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Hydraulic Message from Oxygen-Deficient Roots of Tomato Plants? (Influence of Soil Flooding on Leaf Water Potential, Leaf Expansion, and Synchrony between Stomatal Conductance and Root Hydraulic Conductivity)

Abstract: An important goal in studies of plants stressed at the roots is to establish the relative contributions of hydraulic and chemical messages in mediating adaptive responses of the shoot. In flooded plants, reductions in g, and leaf elongation can occur in the absence of any marked perturbation in leaf water status (Pereira and Kozlowski, 1977; Jackson et al., 1978;Bradford and Hsiao, 1982; Davies, 1986, 1987; Jackson and Hall, 1987), supporting the view that chemical messages predominate. However, it may be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 29 publications
6
47
0
2
Order By: Relevance
“…Our present results confirm those that we reported previously (Else et al, 1995a;Jackson et al, 1996) showing that flooding does not increase delivery of ABA from roots to shoots in the transpiration stream. On the contrary, ABA delivery decreases within 4 h (Fig.…”
Section: Aba As a Positive Message From Flooded Rootssupporting
confidence: 93%
See 1 more Smart Citation
“…Our present results confirm those that we reported previously (Else et al, 1995a;Jackson et al, 1996) showing that flooding does not increase delivery of ABA from roots to shoots in the transpiration stream. On the contrary, ABA delivery decreases within 4 h (Fig.…”
Section: Aba As a Positive Message From Flooded Rootssupporting
confidence: 93%
“…Vol. 11 2,1996 be true sometimes (Hiron and Wright, 1973), we have recently shown that it is not an essential component of the signaling system (Else et al, 1995a).…”
mentioning
confidence: 99%
“…Plant roots become stressed during flooding as the rhizosphere becomes hypoxic or even anoxic. One of the earliest responses to these stresses is a reduced water uptake ability of the roots of stressed plants compared with those of well-drained plants (Schildwacht, 1989;Else et al, 1995Else et al, , 2001). This response is the outcome of decreasing root hydraulic conductance (L 0 ) or conductivity (Lp r ), which is often used as an index of the water uptake ability of roots (e.g., Araki, 2006).…”
mentioning
confidence: 99%
“…Esta reducción ha sido asociado con el cierre estomático en condiciones de encharcamiento en peral (Andersen 1984), arándano (Davies y Flore 1986), ricino (Else et al 2001), tomate (Else et al 1995) y cítricos ).…”
Section: Conductancia Hidráulica Y Encharcamientounclassified
“…Algunos estudios apoyan la hipótesis de que el cierre de estomas en las hojas de plantas encharcadas está causado por la reducción asociada de la conductancia hidráulica (Andersen et al 1984, Davies y Flore 1986, Else et al 1995). Al final del experimento (día 35) la conductancia hidráulica de plantas de CC se redujo aproximadamente en un 89% (Fig.…”
Section: Asfixiaunclassified